Board characteristics and disclosure of corporate anti-corruption policies / Nurfarizan Mazhani Mahmud ... [et al.] - Mahmud, Nurfarizan Mazhani; Mohamed, Intan Salwani; Arshad, Roshayani; Alias, Reskino (Universiti Teknologi MARA, 2021)
This study examined the influence of board characteristics (independent of board members, board expertise, women on board, political directors, and board remunerations) on corporate anti-corruption policies of public listed companies in Malaysia. This study used the Agency Theory to explain the relationship between board characteristics and corporate anti-corruption disclosure based on the Malaysian Code on Corporate Governance (MCCG) 2017. Focusing on empirical evidence of influential board members on corporate commitment to fight corruption; this study utilized content analysis techniques on companies' annual reports and websites to extract data for board characteristics and disclosure of corporate anti-corruption policies. Using OLS regression analysis on 200 companies listed in the main Board of Bursa Malaysia, the finding indicated that board characteristics have an insignificant relationship with corporate communication in fighting corruption. Thus, the study complements the existing literature on corporate governance by focusing on empirical evidence on the linkage between board characteristics and corporate anti-corruption policy disclosure. Further, it also acts as a preliminary study on corporate commitment to provide adequate procedures concerning the MACC Act of corporate liability that took effect in Malaysia in June 2020.